2016
DOI: 10.1112/s1461157016000322
|View full text |Cite
|
Sign up to set email alerts
|

Constructing genus-3 hyperelliptic Jacobians with CM

Abstract: Given a sextic CM field K, we give an explicit method for finding all genus-3 hyperelliptic curves defined over C whose Jacobians are simple and have complex multiplication by the maximal order of this field, via an approximation of their Rosenhain invariants. Building on the work of Weng [J. Ramanujan Math. Soc. 16 (2001) no. 4, 339-372], we give an algorithm which works in complete generality, for any CM sextic field K, and computes minimal polynomials of the Rosenhain invariants for any period matrix of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 18 publications
0
57
0
4
Order By: Relevance
“…By Lemma 3.19, a is uniquely determined by η and u. Furthermore, the proof of Proposition 5.12 showed that all possible values of u for a fixed η are determined up to sign by the integral points of the curve C η defined by equation (3). Therefore,…”
Section: Effectiveness When G =mentioning
confidence: 93%
See 1 more Smart Citation
“…By Lemma 3.19, a is uniquely determined by η and u. Furthermore, the proof of Proposition 5.12 showed that all possible values of u for a fixed η are determined up to sign by the integral points of the curve C η defined by equation (3). Therefore,…”
Section: Effectiveness When G =mentioning
confidence: 93%
“…By Lemma 5.8, h(α(u, η)) ≈ h(u) 2 . Since and each k ≡ 2 mod 3 corresponds to 4 Weil generators given by α(±u k 0 , ±η 0 ), 3 It is not always true that T can be chosen as fundamental units of F we have…”
Section: The Case G =mentioning
confidence: 99%
“…If one acts on the symplectic basis by a matrix in Γ(2), the value of the form given by Lockhart will change by a nonzero constant (the appearance of the principal congruence subgroup of level 2 is related to the use of half-integral theta characteristics to define the form), but if one acts on the symplectic basis by a general element of Sp(6, Z), the value of the form might become zero. As explained in [2], in general to allow for the period matrix to belong to a different Γ(2)-equivalence class, one must attach to the period matrix an element of a set defined by Poor [25], which we call an η-map. Therefore in general one must either modify Lockhart's definition to vary with a map η admitted by the period matrix or use the form Σ 140 , which is nonzero for any hyperelliptic period matrix.…”
Section: Denominators Of Modular Invariants and Primes Of Bad Reductionmentioning
confidence: 99%
“…We begin by describing the maps η that can be attached to a hyperelliptic period matrix. We refer the reader to [25] or [2] for full details.…”
Section: Denominators Of Modular Invariants and Primes Of Bad Reductionmentioning
confidence: 99%
See 1 more Smart Citation